Demographics, Frequency and Pattern of Stroke in COVID-19 Patients: Study from a Tertiary Care Hospital (Medical Forum Monthly, 2022)
Objective: To determine the frequency of different pattern of stroke in Covid 19 patients in a tertiary care hospital of a metropolitan city.Study Design: Descriptive Cross-Sectional studyPlace and Duration of Study: This study was conducted at the department of Neurology and Medicine, Dow university of Health Sciences Karachi, Dow International Medical College Karachi over a period of six months from January, 2021 to December, 2021.Materials and Methods: A total of 59 patients who were admitted with the diagnosis of stroke during the study period were included in the study. Presence of COVID-19 virus were identified by PCR were included in this study, also patient highly suspicious on clinical and radiological grounds were included.Results: COVID test was positive in 22 subjects by nasopharyngeal PCR, 30 subjects positive on oro-pharyngeal PCR and 7 patients were COVID antibody positive. Chest x ray was normal in 4 (6.8%) and abnormal in 55 (93.2%). Majority was having COVID symptoms at presentation, dominating symptom was fever in 54.2% followed by shortness of breath 33.9% and cough 11.9%.Conclusion: We found that stroke is not so common among patients with COVID-19 virus, but patients with stroke have high morbidity and mortality. This study helps to understand the different pattern of Stroke in COVID-19 patient so that the clinician is aware of the all possibilities.